Objective verification of audibility in bone conduction devices. - Persson, Ann-Charlotte; Håkansson, Bo; Fredén Jansson, Karl-Johan; Reinfeldt, Sabine; Eeg-Olofsson, Måns (International Journal of Audiology, 2025)
Objective: To objectively measure audibility in patients wearing bone conduction devices (BCDs) with a new approach using a skin microphone at the patient's forehead. Design: The skin microphone was attached by a softband and shielded by an earmuff. This set-up was confirmed not to be influenced by neither noise floor nor sound bypassing the BCD. Sound field warble tones were used for measuring aided hearing thresholds and maximum power output (MPO) whereas an international speech test signal (ISTS) was presented at different speech levels. Study sample: 29 patients were tested (two were bilateral), 19 used percutaneous, eight used active transcutaneous and two used passive transcutaneous devices. Results: The skin microphone responses at ISTS levels, hearing threshold and MPO, could be obtained in all patients. Two patients with poor audibility are highlighted in this article as examples. After adjusting the gain of the BCD, they were retested with the skin microphone (for verification) and with speech-in-noise tests (for validation). Both tests confirmed an improved audibility after the adjustments. Conclusion: In summary, the proposed measurement of audibility of speech using a skin microphone is a promising method that can be used in a clinical setting for all types of BCDs.